Studi Kualitatif Perilaku Keselamatan dan Kesehatan Kerja pada Pegawai Klinik Esther PKBI Sulawesi Utara - Merdekawati Evangli Weken; Joice Ester Tatilu; Putrinesia Kinanti Ruindungan (Jurnal Ilmiah Kesehatan, 2025)
Esther Clinic PKBI North Sulawesi is a health service facility that provides specialized health services such as counseling and family planning services, pregnancy counseling and examination services, HIV/STI counseling services, reproductive health counseling services, gender-based violence counseling services, and family health counseling services for prospective brides. This study aims to determine the occupational health and safety (OHS) behavior of employees at the Esther Clinic PKBI North Sulawesi. The assessment aspects consist of knowledge, attitudes, and practices concerning OHS. The research is qualitative, utilizing observation methods and in-depth interviews. Informants were selected using purposive techniques from the accessible population. There were five informants, consisting of one Clinic Manager, two Nurses, one Counselor, and one Administrative Staff member. The knowledge and attitude aspects of informants were generally good, but there were still discrepancies in OHS practices. The lack of awareness regarding the use of Personal Protective Equipment is one of the OHS practices that is not yet effective. OHS training has never been conducted, which affects the OHS practices of clinic employees. It is recommended that clinic leaders hold OHS training for all employees of the Esther Clinic PKBI North Sulawesi. The effect of such training can improve safe and healthy work behaviors.